Sentinel lymph node biopsy versus axillary lymph node dissection in breast cancer patients undergoing mastectomy with one to two metastatic sentinel lymph nodes: sub-analysis of the SINODAR-ONE multicentre randomized clinical trial and reopening of enrolment - Corrado Tinterri; Giuseppe Canavese; Wolfgang Gatzemeier; E. Barbieri; Alberto Bottini; Andrea Sagona; Giulia Caraceni; Alberto Testori; Simone Di Maria Grimaldi; Carla Dani; Luca Boni; Paolo Bruzzi; et al. (2023)
The initial results of the SINODAR-ONE randomized clinical trial reported that patients with T1-2 breast cancer and one to two macrometastatic sentinel lymph nodes treated with breast-conserving surgery, sentinel lymph node biopsy only, and adjuvant therapy did not present worse 3-year survival, regional recurrence, or distant recurrence rates compared with those treated with axillary lymph node dissection. To extend the recommendation of axillary lymph node dissection omission even in patients treated with mastectomy, a sub-analysis of the SINODAR-ONE trial is presented here.Patients with T1-2 breast cancer and no more than two metastatic sentinel lymph nodes undergoing mastectomy were analysed. After sentinel lymph node biopsy, patients were randomly assigned to receive either axillary lymph node dissection followed by adjuvant treatment (standard arm) or adjuvant treatment alone (experimental arm). The primary endpoint was overall survival. The secondary endpoint was recurrence-free survival.A total of 218 patients were treated with mastectomy; 111 were randomly assigned to the axillary lymph node dissection group and 107 to the sentinel lymph node biopsy-only group. At a median follow-up of 33.0 months, there were three deaths (two deaths in the axillary lymph node dissection group and one death in the sentinel lymph node biopsy-only group). There were five recurrences in each treatment arm. No axillary lymph node recurrence was observed. The 5-year overall survival rates were 97.8 and 98.7 per cent in the axillary lymph node dissection treatment arm and the sentinel lymph node biopsy-only treatment arm, respectively (P = 0.597). The 5-year recurrence-free survival rates were 95.7 and 94.1 per cent in the axillary lymph node dissection treatment arm and the sentinel lymph node biopsy treatment arm, respectively (P = 0.821).In patients with T1-2 breast cancer and one to two macrometastatic sentinel lymph nodes treated with mastectomy, the overall survival and recurrence-free survival rates of patients treated with sentinel lymph node biopsy only were not inferior to those treated with axillary lymph node dissection. To strengthen the conclusion of the trial, the enrolment of patients treated with mastectomy was reopened as a single-arm experimental study.NCT05160324 (http://www.clinicaltrials.gov).